Network Intrusion Detection Using Machine Learning in Network Intrusion Detection Systems (NIDS) - Arnoldus Jansen; Dery Yuswanto; Budi Styawan; I Made Candra Girinata (Pusat Penelitian dan Pengabdian Politeknik Negeri Tanah Laut, 2025)
Computer network security has become a crucial aspect as dependence on network-based services increases. One important mechanism in maintaining network security is the Network Intrusion Detection System (NIDS), which functions to detect suspicious activity or attacks on network traffic. The traditional signature-based approach has limitations in detecting new attacks (zero-day attacks). Therefore, this study proposes the application of Machine Learning and Deep Learning methods to improve network intrusion detection capabilities. The CIC-IDS2017 dataset was used as the data source because it represents various types of modern network attacks. The research stages included data pre-processing, feature selection, model training, and performance evaluation using accuracy, precision, recall, and F1-score metrics. The models used include Random Forest as a representation of Machine Learning and Long Short-Term Memory (LSTM) as a representation of Deep Learning. The results show that the Deep Learning approach is capable of providing better detection performance on complex attacks compared to conventional Machine Learning methods. This research is expected to serve as a reference in the development of adaptive and accurate network intrusion detection systems.